PEMBELAJARAN BAHASA ARAB - Mukhtar Nuhung (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
Teaching purpose of learning the mother tongue (the default language) is a goal of life, namely as a communication tool to achieve what you want in life, and therefore the motivation for learning is very high. Meanwhile learn foreign languages, such as Arabic (for non-Arab), in general have a purpose as a communication tool and science (culture). However, a foreign language is not used as a language of everyday life, and therefore the motivation to learn Arabic is lower than the mother tongue. Thus the teaching of Arabic (foreigners) should be based on five principles requires that the principle of priority in the preparatory process, and feedback koreksitas principle, the principle of gradual, the principle of appreciation, as well as the correlation and content. Arabic language teaching methods can be classified into two types, namely: first, the method of the traditional / classical, which focuses on language teaching as a science culture. and both modern methods, ie teaching that aims language as a communication tool in modern life. To achieve these objectives must be through effective learning approach yng includes four approaches, namely humanistic, communion-katif, contextual, and structural.